Staphylococcus aureus chronic intramammary infection modifies protein expression of transforming growth factor beta (TGF-β) subfamily components during active involution - Andreotti, Carolina Soledad; Pereyra, Elizabet Amanda Lorena; Baravalle, Celina; Renna, Maria Sol; Ortega, Hugo Hector; Calvinho, Luis Fernando; Dallard, Bibiana Elisabet (2018)
The objectives of this study were to determine whether Staphylococcus aureus chronic intramammary infection (IMI) influences protein expression of TGF-β subfamily components and collagen I and to examine the histomorphometric changes that occur in mammary stroma and parenchyma during active mammary gland involution. Twenty-one Holstein non-pregnant cows in late lactation either uninfected or with chronic natural S. aureus IMI were included in this study. Cows were slaughtered at 7, 14 and 21 d after cessation of milking and samples for immunohistochemical and morphometric analysis were taken. Protein expression of TGF-β1, TGF-β2 and TGF-β3 was significantly higher in chronically infected quarters than in uninfected controls at the three involution stages studied. Immunostaining of TGF-βR1 and TGF-βR3 and collagen I was significantly higher in S. aureus-infected quarters than in uninfected controls at every involution time evaluated. The percentages of tissue area composed of parenchyma and intralobular stroma were significantly higher in S. aureus-infected than in uninfected quarters. Chronic S. aureus mastitis modifies protein expression of the three TGF-β isoforms and type 1 and 3 receptors, which was associated with changes directed to limit the scope of inflammation and injury to the host.